Current scientific evidence for why periodontitis should be included in diabetes management - Borgnakke, Wenche Sylling (Frontiers in Clinical Diabetes and Healthcare, 2024)
This Perspective provides a brief summary of the scientific evidence for the two-way links between periodontal diseases and yperglycemia (diabetes mellitus [DM] and pre-DM). It delivers in a nutshell current scientific evidence for manifestations of hyperglycemia on periodontal health status and effects of periodontal diseases on blood glucose levels and in turn incidence, progression, and complications of diabetes. Of outmost importance is presentation of scientific evidence for the potential of periodontal treatment to lower blood glucose levels, providing a novel, economical tool in DM management. Non-surgical periodontal treatment (“deep cleaning”) can be provided by dental hygienists or dentists in general dental offices, although severe cases should be referred to specialists. Such therapy can decrease costs of DM care and other health care costs for people with DM. The great importance of a healthy oral cavity free of infection and subsequent inflammation -- especially periodontitis that if untreated will cause loosening and eventually loss of affected teeth -- has largely gone unnoticed by the medical community as thehealth care curricula are largely void of content regarding the bi-directional links between oral health and systemic health. Theimportance of keeping disease-free, natural teeth for proper biting and chewing, smiling, self-esteem, and pain avoidance cannot be overestimated. Medical and dental professionals are strongly encouraged to collaborate in patient-centered care for their mutual patients with or at risk for hyperglycemia.